Long-term survival in small cell lung cancer: a case report and review of the literature. (March 2014) - Tartarone, Alfredo; Lerose, Rosa; Ardito, Raffaele; Troiani, Laura; Tedesco, Beatrice; Bozza, Giovanni; Cangiano, Rodolfo; Aieta, Michele
ABSTRACT: : Small cell lung cancer (SCLC) represents approximately 13% of all newly diagnosed lung cancers. SCLC is a very aggressive disease characterized by early locoregional and distant metastases. The median survival is 14–16 months for patients with limited disease and 8–11 months for those with extensive disease, with 20–40% of patients with limited disease and 5% of patients with extensive disease alive at 2 years. This report discusses the case of a long-term SCLC survivor treated with radiotherapy, several lines of chemotherapy and long-acting somatostatin analogs who is alive 7 years after diagnosis, with no evidence of further relapse. In the near future, better identification of prognostic and predictive factors based on models that integrate clinical data and multiple gene expression profiles and the use of novel treatments could increase the number of long-term SCLC survivors.